Countering canons, confronting francophonie: worldwide women's literature in French. (1st December 2009) - Rice, Alison
There is a new proliferation of literary works composed in French by women from around the world. The manifesto, Pour une littrature-monde en franais (2007) bears the signatures of a stunningly diverse handful of women writers such as Maryse Cond, Ananda Devi, Nancy Huston, Anna Mo, and Brina Svit, who exemplify this significant phenomenon. The contributions of authors like Eva Almassy and Chahdortt Djavann to the 2007 book, Pour une littrature-monde (Le Bris and Rouaud 2007), also give evidence of the fact that women from a variety of backgrounds are now making unprecedented contributions to the French-language literary scene, and it is no accident that they are speaking out in favour of a movement that seeks to abolish hierarchical differences between French and Francophone that reign in the publishing world in France. If women from outside France who have chosen to write in French almost uniformly argue for a new conception of francophonie, whether they are from former French colonies or elsewhere, it is because they are keenly aware of the complicated political and economic factors that make up the system in which they publish, and they want their works of fiction to be read and accepted not for ethnological or anthropological reasons, but instead for their creativity and innovation, for their literary value.